BANCASSURANCE: DETERMINANTS OF DEVELOPMENT IN UKRAINE AND POLAND - ALIEKSIEIEV, Ihor; MAZUR, Andriana; YUNKO, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article studies issues regarding the prerequisites for the emergence, formation, and development of bancassurance abroad and in Ukraine. Based on the results of domestic and foreign publications, the issue of the feasibility of introducing bank insurance in modern conditions, characterized by the consequences of the Covid-19 pandemic on the global economy and financial system and martial law for Ukraine, was investigated. The recently expanded introduction of bancassurance in Poland shows that the experience of this country is the closest to the domestic conditions of the functioning of the banking system and the insurance market. The proposed author's approach to studying typology allowed us to compare the scientific and practical methods of scientists and practitioners to the problems of developing, implementing, and implementing the principles of bank insurance. The results of the analysis of statistical data provided by the Ukrainian financial market regulator and the Ministry of Finance of Ukraine made it possible to compare the state and trends in the development of bancassurance in Ukraine in the crisis years of the Covid-19 pandemic and the war period of 2022-2025 with peacetime trends in Poland. The study showed that the Ukrainian banking market is stable even under martial law. Based on the survey by Polish scientists, a conclusion was drawn regarding the possible wave-like course of implementing bancassurance in Poland even under conditions of peaceful development of the economy and finance. The introduction of bancassurance is one of the promising innovative measures in each state's financial system. Research into the practice of cooperation between commercial banks and insurance companies demonstrates the effectiveness of such collaboration. Comparing the experience of Polish and Ukrainian banking institutions cooperating with insurance companies allows us to identify some common characteristics of the activities of such integrated structures, particular achievements of more experienced Polish colleagues, and outline areas for improving the activities of Ukrainian banking and insurance associations.
Keywords: bancassurance; integration of banks and insurance companies; “Allfinanz”